NiO Nanoparticles for Electrochemical Insulin Detection - Jana Shepa; Ivana Šišoláková; Marek Vojtko; Libuše Trnková; Géza Nagy; Iveta Maskaľová; Andrej Oriňak; Renáta Oriňaková (Sensors, 2021)
Diabetes mellitus represents one of the most widespread diseases in civilization nowadays. Since the costs for treating and diagnosing of diabetes represent several billions of dollars per year, a cheap, fast, and simple sensor for diabetes diagnosis is needed. Electrochemical insulin sensors can be considered as a novel approach for diabetes diagnosis. In this study, carbon electrode with electrodeposited NiO nanoparticles was selected as a suitable electrode material for insulin determination. The morphology and surface composition were studied by scanning electron microscopy (SEM), energy dispersive X-ray (EDX) spectroscopy, and X-ray photoelectron spectroscopy (XPS). For a better understanding of insulin determination on NiO-modified electrodes, the mechanism of electrochemical reaction and the kinetic parameters were studied. They were calculated from both voltammetric and amperometric measurements. The modified carbon electrode displayed a wide linear range from 600 nM to 10 µM, a low limit of detection of 19.6 nM, and a high sensitivity of 7.06 µA/µM. The electrodes were stable for 30 cycles and were able to detect insulin even in bovine blood serum. Additionally, the temperature stability of this electrode and its storage conditions were studied with appropriate outcomes. The above results show the high promise of this electrode for detecting insulin in clinical samples.